Best of the Lion King [compact disc]. (Walt Disney Records, 2011)
From the big screen to the Broadway stage, the Lion King has become one of the most beloved stories in the history of Disney. To commemorate its 2011 re-release on DVD, this collection pulls together the best music from the various Lion King projects.